1995
DOI: 10.1002/etc.5620141111
|View full text |Cite
|
Sign up to set email alerts
|

Metal and arsenic impacts to soils, vegetation communities and wildlife habitat in southwest Montana uplands contaminated by smelter emissions: I. Field evaluation

Abstract: Concentrations of arsenic and metals in soils surrounding a smelter in southwest Montana were correlated with vegetative community structure and composition and wildlife habitat quality. Soils in the uplands surrounding the smelter were highly enriched with arsenic and metals. Concentrations of these analytes decreased with distance from the smelter and with soil depth, suggesting that the smelter is the source of the enrichment. In enriched areas, marked modifications to the native vegetation community struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…(Faustand and Christians 2000). Fourth, in view of the ecosystem, heavy metals could be transported and magnified in the food chain, and pose a potential hazard to human health (Galbraith et al 1995;Ginocchio 2000;Antoniadis and Mckinley 2003). Although rubbish compost is nutrient-enriched for plant requirements (Manna et al 2001), heavy metals in rubbish compost would result in their accumulation in plants and could affect plant growth.…”
Section: Discussionmentioning
confidence: 98%
“…(Faustand and Christians 2000). Fourth, in view of the ecosystem, heavy metals could be transported and magnified in the food chain, and pose a potential hazard to human health (Galbraith et al 1995;Ginocchio 2000;Antoniadis and Mckinley 2003). Although rubbish compost is nutrient-enriched for plant requirements (Manna et al 2001), heavy metals in rubbish compost would result in their accumulation in plants and could affect plant growth.…”
Section: Discussionmentioning
confidence: 98%
“…Investigations over the last several decades (Mankovska and Steinnes 1995;Kozlowski 2000;Kozlov and Zvereva 2007) have demonstrated that forest ecosystems are vulnerable to human-induced environmental stresses, resulting in a progressive loss of biodiversity and general declines in forest health. Adverse impacts to the forest ecosystems lead to concomitant changes in the quality and extent of wildlife habitat (Galbraith et al 1995). Such studies indicate a large potential for anthropogenically caused changes in forest environments.…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium (Cd) and arsenic (As) are two of the most common global environmental pollutants, which enter the environment through metal mining and smelting activities, industrial and urban waste, combustion of fossil fuels, and application of agricultural fertilizers (Sneller et al, 2000;Galbraith et al, 1995;Maclean and Langille, 1981;Abedin et al, 2002aAbedin et al, , 2002b). The Cd-or As-polluted water for drinking and crop irrigation causes serious health problems to human and other organisms (Watanabe et al, 2000;Chen et al, 1995;Liao et al, 2005;Mandal et al, 1997;Quaghebeur and Rengel, 2003).…”
Section: Introductionmentioning
confidence: 99%